Tes Diagnostik Miskonsepsi Peserta Didik pada Materi Gaya Kelas IV Sekolah Dasar - Tsania, Aulia; Kurniawati, Wahyu (Edukasi: Jurnal Penelitian dan Artikel Pendidikan, 2024)
Science in general teaches to develop reasoning skills and be able for understand concepts, but in reality science learning there are still students who experience misconceptions. The purpose of the study is to determine the magnitude of misconceptions in 4th-grade students of SD Negeri Ngrukeman and to find out the causes of misconceptions, so that they can determine the right solution to the problem. This research uses quantitative descriptive research. The data collection technique used diagnostic tests and the subjects in this study were 4th-grade students of SD Negeri Ngrukeman. Based on the results of the diagnostic test, it is known that the percentage of students' misconceptions on the topic "The Effect of Force on Objects" is 65%, the topic "Magnets, a Magical Object" is 59%, the topic "Elastic Objects" is 31%, the topic "Why We Don't Float in the Air" is 11%. The causal factors of the misconceptions themselves are 1) students' wrong preconceptions; 2) ineffective learning models; 3) teachers repeating material when students experience misconceptions; and 4) teaching materials that have not facilitated concept understanding properly. The solution that can be done is the need to develop teaching materials that contain practices and learning models that can reduce misconceptions.